Non-tariff measures and standards in trade and global value chains - John C. Beghin; Miet Maertens; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2015)
We assess the literature on public and private quality standards and their impact in food markets, international trade, and global supply chains. We focus on their effects on welfare, trade, industrial organization, and labor markets and with special attention to the North-South context. We also attempt to better characterize when these measures constitute protectionism, a complicate task. We look at studies investigating public and private standards and across various quantitative approaches and countries. These standards have complex effects. The evidence is mixed regarding standards as catalyst for or impediment against trade and development, reflecting the complexity of these effects and their specificity to industries and countries. The analysis of standard - like nontariff measures and their impacts does not lead to sweeping prescriptions for policy reforms. We identify more modest prescriptions and make some recommendation s for fruitful research directions.
Keywords: F13; F15; Q17; O19; 330; supply chain; standards; nontariff measures; SPS; NTM; trade; welfare; North-South